Thin Layer Chromatography of Secondary Metabolite Profiles and Determination of Total Flavonoid Levels of the Sawi Langit Extract that Growing on Peatlands - Carolina, Feliya; Nastiti, Kunti; Rizali, Muhammad (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Peatland is a type of soil with a high organic content, typically more than 65 percent organic matter, high acidity, and low nutrient content. Vernonia cinerea, also known as Sawi Langit (Vernonia cinerea L.) in Indonesia, is one of the nutritious plants. The community uses this herb to treat fevers, wounds, discomfort, and ulcers. The secondary metabolite concentration of plants in peatlands is affected by nutrients such as carbon, nitrogen, and pH. Find out the secondary metabolite content of Sawi Langit leaf extract and the total flavonoid levels that grown on peatlands. The Rf value was estimated after the descriptive observational approach was obtained from the Thin Layer Chromatography (TLC) profile of secondary metabolites with spray reagents, and the quantitative data was determined by UV-Vis spectrophotometry. Sawi Langit plants were found growing on peatlands with a pH of 3.77, N-total of 1.51%, and C-Organic of 4.16%. The best eluent for separating compounds is chloroform: methanol: water (2:5:3) for flavonoid compounds, ethyl acetate: methanol: water (16:1:2) for alkaloid compounds, chloroform: methanol (9:1) for steroid compounds, n-hexane: ethyl acetate (12:8) for terpenoid compounds, ethyl acetic: chloroform: acetic acid (15:5:2) for tannin compounds, and chloroform: ethanol: water (10:6:1) for saponin compounds. Sawi langit leaf extract has a total flavonoid concentration of 5.527 mgQE (Quersetin Equivalent)/g. Flavonoid, alkaloids, steroids, terpenoids, tannins, and saponins compounds were found in the TLC profile of Sawi Langit leaf extract, and the total flavonoid content of the leaf extract of Sawi Langit was 5.527 mgQE (Quersetin Equivalent)/g.